2020
DOI: 10.1021/acs.jnatprod.9b01169
|View full text |Cite
|
Sign up to set email alerts
|

Carneic Acids from an Endophytic Phomopsis sp. as Dengue Virus Polymerase Inhibitors

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The absolute configurations of C-3, C-11, C-17, and C-21 in 2 were assigned as 3R, 11R, 17R, and 21S based on the negative Cotton effect at 225 nm in ECD spectra ( Figure 4B and Figure S17) and calculated ECD spectra ( Figure 4B). 5.75)/H-23 (δH 0.52) indicated that these protons located on the β-orientation of the cyclopentane ring. Besides, the ROESY correlations from H-21 (δH 2.68) to H-4 (δH 6.89) indicated that the cyclopentane ring was orthogonal to the plane of the indoxyl ring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absolute configurations of C-3, C-11, C-17, and C-21 in 2 were assigned as 3R, 11R, 17R, and 21S based on the negative Cotton effect at 225 nm in ECD spectra ( Figure 4B and Figure S17) and calculated ECD spectra ( Figure 4B). 5.75)/H-23 (δH 0.52) indicated that these protons located on the β-orientation of the cyclopentane ring. Besides, the ROESY correlations from H-21 (δH 2.68) to H-4 (δH 6.89) indicated that the cyclopentane ring was orthogonal to the plane of the indoxyl ring.…”
Section: Resultsmentioning
confidence: 99%
“…Endophytic fungi are prolific microbial resources for the production ability of many biologically active secondary metabolites, which can help the host to resist pathogenic microorganisms [2]. Various endophytic fungi have drawn substantial attention due to their potential to produce chemically diverse and biologically active secondary metabolites with anti-cancer, anti-microbial, anti-viral, and insecticidal activities [3][4][5][6]. In our continuous searching for novel bioactive secondary metabolites from marine endophytic fungi [7][8][9], the Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ) and the lower inhibitory potential of the compounds when this subunit is oxidized at C-18. They further listed the β-OH group at C-9 in compound 15 as likely responsible for the activity of this compound on the polymerase [ 22 ]. The literature indicates that some molecules selected from the Dacrydium balansae species did not show the same potential as isolated biflavonoids (compounds 28 , 36 , 7 , 29 ), thus suggesting, through the comparison of chemical structures, the importance of the dimeric nature of biflavonoids (Fig.…”
Section: Molecular Structures Of Isolated Compounds With the Potentia...mentioning
confidence: 99%
“…f Carneic acids C (12) 19.0 RdRp-DENV b [ 22 ] Phomopsis sp . f Carneic acids D (13) 19.0 RdRp-DENV b [ 22 ] Phomopsis sp . f Carneic acids F (15) 11.8 RdRp-DENV b [ 22 ] Phomopsis sp .…”
Section: Molecular Structures Of Isolated Compounds With the Potentia...mentioning
confidence: 99%